Regulatory T Cells Conditioned Media Stimulates Migration in HaCaT Keratinocytes: Involvement of Wound Healing - Kim D; Lo E; Kim D; Kang J (Dove Medical Press, 2020)
Dongsoo Kim, Eunji Lo, Dongju Kim, Junghwa Kang Research & Development, IMMUNISBIO CO. Ltd., B2, International ST. Mary’s Hospital MTP Mall, Seo-gu, Incheon, KoreaCorrespondence: Junghwa KangResearch & Development, IMMUNISBIO CO. Ltd., B2, International ST. Mary’s Hospital MTP Mall, 31, Simgok-ro 100 Beon-gil, Seo-gu, Incheon, KoreaTel +82-32-715-5868Fax +82-32-715-5869Email kjunghwa@immunisbio.comPurpose: Regulatory T (Treg) cells, a type of immune cell, play a very important role in the immune response as a subpopulation of T cells. In this study, we investigated the effects of Treg cells conditioned media (CM) on cell migration. Various cytokines and growth factors of Treg cells CM can effect on re-epithelialization stage during the wound healing.Methods: Isolated CD4+CD25+ Treg cells from Peripheral Blood Mononuclear Cells (PBMCs) were cultured and CM obtained. HaCaT keratinocytes were treated with various concentration of Treg cells CM. Cell migration, proliferation and expression of proteins that are related to the Epithelial-Mesenchymal Transition (EMT) process, matrix metalloproteinase-1 (MMP-1) were analyzed.Results: Above 90% CD4+CD25+ Treg cells were obtained from CD8+ depleted PBMCs and the CM have various cytokines and growth factors.One percent and 5% concentration of Treg cells CM increased HaCaT keratinocytes migration. The Treg cells CM stimulated EMT, which led to the down-regulation of E-cadherin in the HaCaT keratinocytes at the wound edge. The Treg cells CM increased MMP-1, which is involved in tissue remodeling.Conclusion: Our results suggest that Treg cells CM which has various cytokines and growth factors promote wound healing by stimulating HaCaT keratinocytes migration.Keywords: regulatory T cells, cells conditioned media; CM, keratinocytes, migration, Epithelial-Mesenchymal Transition; EMT, matrix mjetalloproteinase-1; MMP-1, wound healing